Design and Simulation of Idling Start-Stop System on Motorcycles - Hamidoon, Harith; Sulaiman, Syabillah (Progress in Engineering Application and Technology, 2021)
The idling start-stop system is one of the system that has implemented into the motorcycles nowadays. Most of the automotive industry always compete to develop new system technology into the vehicle markets. This system mostly found in hi-tech motorcycles with relatively highly prices in the market compared to the low-end motorcycle. In this study, a start-stop system was been designed and simulated by using the TinkerCAD software. There are several components required to create the simulation of idling start-stop system such as DC motor, potentiometer, Arduino and LCD. The circuit and coding has been constructed based on the collection of information from previous research study. The result shows how the idling start-stop system works, the results of the simulation has been collected and discussed. In a future, this simulation can be used as a reference during development process of an actual system start-stop kit.